Automatisasi Proses Robotik dan Dampaknya Pada Akuntansi - Sutari Sri Rejeki; Pemilia Sulistyowati (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
This study aims to examine the consequences of human-machine collaboration in accounting and develop methods to address potential negative impacts such as human-robot competition, accidental changes in organizational structure, skills decline and skill building, knowledge management, and knowledge bias. The potential of RPA in accounting process automation is large and can replace the role of accountants significantly. This resulted in the loss of entry-level accounting positions, but also created new roles as business advisors and RPA transformation leaders. Accountants of the future will need to improve their soft, technological and data management skills. Research is needed to integrate these skills in accounting education and identify the negative impacts of robot use, as well as the financial and non-financial effects of RPA implementation. This study highlights the impact and potential of RPA in accounting while also providing a new picture of RPA automation in accounting processes with an emphasis on the evolutionary nature of RPA, so it provides insight into how this technology can transform the accounting profession. This study uses the literature review method used as a basis to suggest future research directions related to challenges and problems associated with RPA in accounting. The results of this study show that, RPA has the potential to transform the field of accounting and highlight several research areas in the future, including the consequences of human-machine collaboration, the limitations and barriers of automation, and the development of new roles and skills in accounting education. The study suggests future research directions to address RPA-related challenges and issues in accounting. In addition, understanding the full impact and potential of RPA in accounting is needed before continuing research into the same area.